Corrosão de armaduras em meios aquosos e porosos de argamassas com agregados alternativos (ACBC e LETA) - Rezende, Mariana de Almeida Motta (2022)
About 4% of the GDP of industrialized countries is destined to the maintenance of materials deteriorated by corrosion and the corrosion of reinforcements contributes to a significant portion of this percentage. Another problem in civil construction is the exacerbated use of natural resources, such as sand and gravel, used as aggregates for the production of concrete. Over time, these resources became scarce and the use of recycled aggregates became necessary. The author's research group has been working with eco-efficient waste for two decades, and this knowledge was combined with the general objective of this work, which was to evaluate the corrosion of reinforcement in cementitious composites with the incorporation of two residues separately: sugarcane bagasse ash sand (SBAS) and water treatment sludge (WTS), both used as fine aggregate in concrete pore solutions (CPS) and in cement composite samples. The innovation of this work lies in the use of the corrosion assessment technique in CPS for concrete with residues. For this, carbon steel samples were immersed in pore solutions of cementitious composites with SBAS and WTS in pure solutions and solutions contaminated with aggressive agents to the reinforcement (chlorides and carbonates). In an electrochemical cell, the monitoring of the open circuit potential, the electrochemical impedance spectroscopy and the linear scanning polarization were carried out to verify the corrosion of the steel in the different solutions studied. In addition, the results obtained were compared to the results of similar evaluation on cementitious composites of the same traces of WTS and SBAS. Based on the analyzes carried out, it was possible to conclude that the incorporation of SBAS is beneficial in terms of corrosion resistance of reinforcements, and can be used as a fine aggregate to replace 30% by mass with natural sand in concrete for structural purposes in marine environments. However, 3% of LETA replacing natural sand in concrete caused the passivation film not to form properly on the reinforcement. Therefore, in this case, concrete with this WTS percentage cannot be recommended for structural purposes in a marine environment.